UJI KETELITIAN DTM ALOS PALSAR TERHADAP PENGUKURAN KOMBINASI DGNSS-ALTIMETER - Atriyon Julzarika; Esthi Kurnia Dewi (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2018)
Height model is model include the information of height data and its coordinate in earth surface. Height model is one of the geological parameters that are useful for a variety of applications of survey and mapping. Height model in the form of Digital Surface Model, Digital Elevation Model, Digital Terrain Model, Digital Terrain Elevation Digital, Geoid, and others. Height model can be made with data, aerial photographs, satellite imagery, and Interferometry Synthetic Aperture Radar. This research aims to test the vertical accuracy of ALOS PALSAR against the combination measurement of Differential Global Navigation Satellite System-Altimeter. Digital Surface Model is made from images of ALOS PALSAR with interferometry Synthetic Aperture Radar methods. Digital Elevation Model retrieved after height error correction and terrain correction of Digital Surface Model. Digital Terrain Model obtained after the integration of river features and bathymetry in Digital Elevation Model ALOS PALSAR.Then do the vertical accuracy test of ALOS PALSAR againts the combination measurement of Differential Global Navigation Satellite systems-Altimeter.Differential Global Navigation Satellite systems received the data from the GPS, Beidou, GLONASS, SBAS, MSAS, Gagan, and QZSS satellite and uses period of 14 days before the measurement with the time in measurement. During the measurement for processing the position data and height value. Differential Global Navigation Satellite systems was connected with server of internet provider. Region of vertical accuracy test is in Merauke regency in 2016. The tolerance standard of this vertical accuracy test refers to National Standard for Spatial Data Accuracy in 1.96 σ (95%) tolerance. From the two vertical accuracy test, height difference test and tranverse profile test, Digital Terrain Model ALOS PALSAR have fulfilled tolerance in 4,996e- 16 (~0) and 80,791 cm so it can be used for various applications of survey and mapping for 1:10.000 scale.ABSTRAKModel tinggi adalah model yang meliputi informasi data tinggi dan koordinatnya di permukaan bumi. Model tinggi merupakan salah satu parameter geologi yang bermanfaat untuk berbagai aplikasi survei dan pemetaan. Model tinggi berupa model permukaan digital, model elevasi digital, model terrain digital, model terrain elevasi digital, Geoid, dan lain-lain. Model tinggi dapat dibuat dengan data lapangan, foto udara, interferometri radar sintetis, dan citra satelit. Penelitian ini bertujuan untuk melakukan uji akurasi vertikal model terrain digital ALOS PALSAR terhadap pengukuran kombinasi diferensial sistem satelit navigasi global-Altimeter. Model permukaan digital dibuat dari citra ALOS PALSAR dengan metode interferometri radar sintetis. Model elevasi digital diperoleh setelah dilakukan koreksi kesalahan tinggi dan koreksi terrain model permukaan digital. Model terrain digital diperoleh setelah dilakukan integrasi fitur sungai dan batimetri terhadap model permukaan digital. Model terrain digital ALOS PALSAR dilakukan uji akurasi vertikal dengan pengukuran kombinasi diferensial sistem satelit navigasi global-Altimeter. Diferensial sistem satelit navigasi global menerima data dari satelit GPS, Glonass, Beidou, Gagan, MSAS, SBAS, dan QZSS dan menggunakan periode waktu 14 hari sebelum pengukuran dengan waktu saat pengukuran. Selama pengukuran,untuk mengolah data posisi dan ketinggian. Diferensial sistem satelit navigasi global dikoneksikan dengan server melalui jaringan internet selular. Lokasi uji akurasi vertikal dilakukan di Kabupaten Merauke pada tahun 2016. Standar toleransi uji akurasi vertikal ini mengacu kepada toleransi standar nasional untuk akurasi data spasial sebesar 1,96σ (95 %). Dari dua jenis uji akurasi vertikal, yakni uji beda tinggi dan uji profil melintang, model terrain digital ALOS PALSAR telah memenuhi toleransi sebesar 4,996e-16 (~0)dan 80,791 cm sehinggadapat digunakan untuk berbagai aplikasi survei dan pemetaan skala 1:10.000.